Penerapan Problem Based Learning pada Pembelajaran Kalor untuk Meningkatkan Hasil Belajar Siswa MI Al-Khoeriyah Manonjaya - Leli Nurlayali (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2021)
Learning outcomes are the level of success of each student in studying a subject matter in school obtained from the test results. In fact, students’ learning outcomes in Class V MI Al-Khoeriyah have not reached the minimum completeness criteria. One of the learning models that can improve students' understanding and learning outcomes is the Problem Based Learning. The application of Problem Based Learning learning is expected to create quality learning outcomes. This study uses a classroom action research method that aims to determine the planning, implementation, and success of the application of PBL in heat learning to improve student learning outcomes at MI Al-Khoeriyah Manonjaya. The subjects were 9 female students and 11 male students in class V MI Al-Khoeriyah Manonjaya. Data were obtained through observation and interview instruments. Based on the results of the study, it was found that the process of planning, implementing, and successfully implementing the PBL learning model in learning to improve student learning outcomes was in accordance with the steps set into three cycles. The students' average score, which was originally 55.7, increased to 59.09 in the first cycle, 75 in the second cycle, and 85 in the third cycle.